IMPLEMENTATION OF TRUE OR FALSE LEARNING STRATEGY TO IMPROVE LEARNING ACHIEVEMENT IN THE SUBJECT OF CREED AND MORALS OF GRADE VII STUDENT MTs AL MUHAJIRIN BANDAR LAMPUNG - Setiawati, Aisyah; Putra, Arizal Eka; Basyar, Muslim (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2024)
Education is a crucial factor in individual development and national progress, especially in character and moral formation. The subject of akidah akhlak in Madrasah Tsanawiyah plays a significant role in shaping students' personalities. However, in practice, there are often issues with ineffective teaching methods, such as the dominance of lecture-based instruction, which leads to passive student participation. This impacts students' academic performance. This study aims to analyze the application of the true or false teaching strategy in the akidah akhlak subject to improve students' academic achievement in class VII at MTs Al Muhajirin Bandar Lampung. This research uses the Classroom Action Research (CAR) approach, which consists of two cycles. Each cycle involves planning, implementation, observation, and reflection. The results of the study indicate that the application of the true or false strategy can increase student engagement in learning and improve academic performance. In the first cycle, although there was improvement, the average score did not meet the expected completion criteria. However, in the second cycle, a significant improvement was observed, with the average score reaching 80 and the learning completeness reaching 82.14%. This shows that the true or false teaching strategy has the potential to enhance students' understanding of akidah akhlak and boost their academic performance.